Estrogen receptors alpha and beta in male and female gerbil prostates - Rochel-Maia, Sabrina S.; Santos, Fernanda C.A. [UNESP]; Alonso-Magdalena, Paloma; Góes, Rejane Maira [UNESP]; Vilamaior, Patricia S.L. [UNESP]; Warner, Margaret; Gustafsson, Jan-Åke; Taboga, Sebastião Roberto [UNESP] (Oxford University Press (OUP), 2013)
The Mongolian gerbil (Meriones unguiculatus, Gerbilinae: Muridae) is useful for prostate studies, because both males and females spontaneously develop prostatic disorders with age. Estrogens regulate prostate homeostasis via two estrogen receptors, ER alpha (ESR1) and ER beta (ESR2), but the cellular distribution and regulation of these receptors in the gerbil prostate has not been described. Both receptors were localized by immunohistochemistry in the ventral prostate of intact male and female gerbils, in males 7 and 21 days after castration, and in females treated with testosterone for 7 and 21 days. In male and female adult gerbils, ER alpha was detected mainly in prostatic stromal cells, whereas ER beta was present mostly in secretory and basal cells. More ER alpha-positive stromal cells were found in females than in males, as was a reduction toward the male value in females treated with testosterone. Castration did not alter ER alpha expression. Testosterone was necessary for maintenance of ER beta in the male prostate epithelium: ER beta expression declined markedly in prostates of males older than 1 yr, and castration of 4-mo-old males caused a reduction in ER beta to levels seen in 1-yr-old males. Because ER beta is an antiproliferative receptor, its loss with age may predispose the aging gerbil to proliferative diseases of the prostate. © 2013 by the Society for the Study of Reproduction, Inc.
Keywords: Castration; Estradiol/estradiol receptor; Estrogen receptor; Female; Gerbil; Prostate; Steroid hormones/steroid hormone receptors; Stroma; Testosterone; estrogen receptor alpha; estrogen receptor beta; testosterone; animal experiment; animal tissue; basal cell; castration; cellular distribution; controlled study; female; gerbil; immunohistochemistry; male; nonhuman; priority journal; prostate ventral lobe; protein expression; protein localization; secretory cell; stroma cell; Animals; Estrogen Receptor alpha; Estrogen Receptor beta; Estrous Cycle; Gene Expression Regulation; Gerbillinae; Male; Random Allocation